2021
DOI: 10.3934/jimo.2020084
|View full text |Cite
|
Sign up to set email alerts
|

The optimal solution to a principal-agent problem with unknown agent ability

Abstract: We investigate a principal-agent model featured with unknown agent ability. Under the exponential utilities, the necessary and sufficient conditions of the incentive contract are derived by utilizing the martingale and variational methods, and the solutions of the optimal contracts are obtained by using the stochastic maximum principle. The ability uncertainty reduces the principal's ability of incentive provision. It is shown that as time goes by, the information about the ability accumulates, giving the agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Three groups of studies were related to this work. Our study is related to the fast-growing literature that emphasizes information asymmetry in dynamic contracting problems (Giat and Subramanian, 2013;He et al, 2017;Lai et al, 2021). He et al (2017) extended the model of DeMarzo and Sannikov (2017) by introducing uncertainty and learning into a long-term contracting problem.…”
Section: Related Literaturementioning
confidence: 98%
See 4 more Smart Citations
“…Three groups of studies were related to this work. Our study is related to the fast-growing literature that emphasizes information asymmetry in dynamic contracting problems (Giat and Subramanian, 2013;He et al, 2017;Lai et al, 2021). He et al (2017) extended the model of DeMarzo and Sannikov (2017) by introducing uncertainty and learning into a long-term contracting problem.…”
Section: Related Literaturementioning
confidence: 98%
“…Using the dynamic programming technique, they derived the optimal contract, which is contingent on the information rent that the principal rewards the agent. Lai et al (2021) investigated a principal-agent model featuring unknown agent's ability utilizing martingale and variational methods. They found that the agent's ability is completely revealed as the contractual duration tends to be infinite (long-term), and both the agent's payment and the principal's consumption depend on the agent's promised utility.…”
Section: Related Literaturementioning
confidence: 99%
See 3 more Smart Citations